Comparative analysis of positive and negative consequences of the dissemination of conspiracy theories. - Babajanyan, Levon (Bulletin of Yerevan University E: Philosophy, Psychology, 2024)
The article is dedicated to a comparative analysis of the assessment of socio-psychological, socio-political, and epistemological consequences stemming from the propagation of conspiracy theories. Particularly, the article demonstrates that, despite the prevalent negative reputation attached to the dissemination of conspiracy theories within academic circles of the humanities and social sciences, their ramifications cannot be unequivocally categorized as negative phenomena. The article draws upon interdisciplinary empirical and theoretical research findings concerning the issue, encompassing socio-psychological, socio-political, and epistemological consequences of conspiracy theory dissemination. Negative consequences outlined include deepening public distrust in political institutions, threats to democracy, rejection of scientific knowledge, and manifestations of socio-psychological vulnerability. Conversely, positive consequences are identified as heightened political transparency and accountability, the revelation of actual conspiracies and cognitive adaptation within the individual’s worldview. The comparative analysis concludes that initially, the negative consequences of conspiracy theory dissemination outweigh the positive ones; however, the positive consequences exhibit short-term effects while the negative consequences have long-term implications. The findings of the article hold relevance for humanitarian and social researches, in shaping state and public policy development.
Keywords: Conspiracy Theories; Conspiracy Thinking; Cognitive Biases; Comparative Analysis; Political Narratives; Populism; Political Alienation